2012
DOI: 10.1111/j.1346-8138.2012.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and psoriatic risk: A meta‐analysis of case–control studies

Abstract: Psoriasis is one of the most common dermatological disorders. The association between alcohol consumption and psoriasis has been inconsistent among studies. To examine the magnitude of the risk of developing psoriasis for drinking populations compared to those with non-drinking, and to determine causes of the variation in odds ratios (OR) between various case-control studies, we performed a comprehensive published work search and a meta-analysis of case-control studies considering prevalence. We did electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
(51 reference statements)
1
31
1
6
Order By: Relevance
“…Further investigation of the potential impact of these factors on treatment response in patients with psoriasis is warranted, especially as smoking may be an independent risk factor for psoriasis in both women and men (Li et al, 2012). Similarly, alcohol consumption (Zhu et al, 2012). In addition, examination of the impact of some of these factors in more diverse populations (e.g., elderly patients with comorbidities) and quantification of the prevalence of such factors in future studies may also help decision making in clinical practice.…”
Section: Study Results In Perspectivementioning
confidence: 98%
“…Further investigation of the potential impact of these factors on treatment response in patients with psoriasis is warranted, especially as smoking may be an independent risk factor for psoriasis in both women and men (Li et al, 2012). Similarly, alcohol consumption (Zhu et al, 2012). In addition, examination of the impact of some of these factors in more diverse populations (e.g., elderly patients with comorbidities) and quantification of the prevalence of such factors in future studies may also help decision making in clinical practice.…”
Section: Study Results In Perspectivementioning
confidence: 98%
“…Recently, a metaanalysis of case-control studies showed that the overall odds ratio of psoriasis for drinking persons compared to those with non-drinking habits was 1.531 (P = 0.002), suggesting that alcohol consumption is associated with an increased risk of psoriasis. 31 However, the connection between psoriasis and alcohol consumption remains complex and has yet to be fully elucidated. Several other studies have not shown a significant correlation between alcohol consumption and psoriasis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…16,20,32 Several mechanisms by which alcohol may induce psoriasis have been proposed, including upregulation of pro-inflammatory cytokines in various cell types, proliferation and activation of lymphocytes, hyperproliferation of keratinocytes as well as an increased risk of infection which can precipitate psoriasis. 31,[33][34][35] Acute bacterial and viral infections have been associated with the onset or exacerbation of psoriasis. 36,37 Streptococcal infections are often triggers of guttate psoriasis, especially in children and young adults.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Psoriasis in heavy drinkers tends to be more severe, more extensive and their lesions are usually more inflamed [7,8]. A number of case-control studies confirmed the association of psoriasis with alcohol abuse and recently a comprehensive meta-analysis of these published studies was also conducted showing a significant link between psoriatic risk and alcohol consumption in drinking versus non-drinking subjects [9]. Alcohol misuse is a major cause of both acute and chronic liver disease and TNF-α, a key cytokine in psoriasis pathogenesis, has been found to have a crucial role in this process [10,11].…”
Section: Introductionmentioning
confidence: 99%